Jack Welch and the Ge Way. Wawasan manajemen dan rahasia kepemimpinan CEO Legendaris - [Tidak Terdaftar] (Andi Offset, 2001)
Jack Welch and the Ge Way. Wawasan manajemen dan rahasia kepemimpinan CEO..